Treatment of fish processing waste water in UASB reactor regarding fat and chloride levels - Ome, Santos V. (1998)
The feasibility of using UASB reactor for the treatment of fish processing waste waters of different fat and chloride levels was determined in this study. Fish waste water ( 3 -4 g COD.1 -1) was prepared from homogenized raw tuna and sardines to obtain mixtures similar to untreated fish canning waste water. The COD removal in treating high-fat waste water (i.e. fat-COD is 45 -47% of total COD) was 87 - 97%. About 65% of the removed COD is converted to methane and the rest (about 35%) is removed as floating solids. the COD removed in treating low-fat waste water (i.e fat-COD is 5-9% of total COD) is 74 -89% of the influent total COD. Of the removed COD, 76 -80% was converted to methane. The hydrolysed COD in the low-fat fish waste water is about 76% and 57% respectively, of the influent total COD. In the treatment of high-fat waste water, the degradation of fats is rate-limiting. Chlorides inhibited the methane formation during the early stage of the UASB reactor run but methane production increased in the later stage indicating that sludge adaptation to high chloride level is possible.
Computer print-out.
Thesis (M.S. Chemical Engineering)--University of the Philippines Diliman.
Keywords: Factory and trade waste -- Biodegradation -- Philippines; Canned fish; Factory and trade waste -- Purification -- Philippines; Sewage sludge; Sewage